2016
DOI: 10.1287/mnsc.2015.2198
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguity Attitudes in a Large Representative Sample

Abstract: We introduce a tractable method for measuring ambiguity attitudes, which requires only three observations and five minutes per subject, and we apply this method in a large representative sample. In addition to ambiguity aversion, we confirm a-insensitivity, a new ambiguity component recently found in laboratory studies. A-insensitivity means that people insufficiently discriminate between different levels of likelihood, often treating all likelihoods as fifty-fifty, which results in the overweighting of extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
181
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(200 citation statements)
references
References 93 publications
19
181
0
Order By: Relevance
“…Note that problem 6-Ambiguity (7-Ambiguity) is the ambiguous equivalent of problem 2-Risk (4-Risk). We do not have model-based predictions but since individuals are usually ambiguity averse (see, e.g., Ellsberg 1961;Dimmock et al 2015), we considered that ambiguity may have similar effects as increased risk aversion in allocation problems under risk. Table 11 shows descriptive statistics on giving in the presence of ambiguity.…”
Section: Allocation Problems Characterized By Ambiguitymentioning
confidence: 99%
“…Note that problem 6-Ambiguity (7-Ambiguity) is the ambiguous equivalent of problem 2-Risk (4-Risk). We do not have model-based predictions but since individuals are usually ambiguity averse (see, e.g., Ellsberg 1961;Dimmock et al 2015), we considered that ambiguity may have similar effects as increased risk aversion in allocation problems under risk. Table 11 shows descriptive statistics on giving in the presence of ambiguity.…”
Section: Allocation Problems Characterized By Ambiguitymentioning
confidence: 99%
“…Recently, Dimmock et al (2015) found that stock market participation, as well as the ownership of small businesses, is negatively correlated with ambiguity-induced insensitivity. To the extent that such slopes become more extreme as stakes increase, this may, indeed, be an important factor for the explanation of such decisions, given the overestimation of small probabilities of losses and underestimation of moderateto-large probabilities of gains that derive from it.…”
Section: Discussionmentioning
confidence: 99%
“…9 The aim of 7 For example, Stahl (2014), finds that 60 % of subjects choose close to randomly; Charness et al (2013) find that 20 % of subjects choose incoherently; Duersch et al (2013) find that, after a short interval, 29 % choose differently in repetitions of the same question; and Dimmock et al (2015) find that up to 45 % do not choose according to their previously stated preferences. 8 If one views adherence to the compound lottery axiom as a requirement of rationality, then the results in Halevy (2007) show that ambiguity aversion is absent among those who are rational in this sense.…”
Section: Methodsmentioning
confidence: 99%
“…9 A probability-matching approach is also used in MacCrimmon and Larsson (1979), Kahn and Sarin (1988), and Viscusi and Magat (1992). Dimmock et al (2015) provide theoretical support for this method. Fig.…”
Section: Methodsmentioning
confidence: 99%